Electrostatic Charge‐Mediated Apoptotic Vesicle Biodistribution Attenuates Sepsis by Switching Neutrophil NETosis to Apoptosis. Issue 20 (15th April 2022) - Ou, Qianmin; Tan, Lingping; Shao, Yiting; Lei, Fangcao; Huang, Weiying; Yang, Ning; Qu, Yan; Cao, Zeyuan; Niu, Luhan; Liu, Yao; Kou, Xiaoxing; Shi, Songtao
Abstract: Mesenchymal stem cell (MSC) therapy can attenuate organ damage and reduce mortality in sepsis; however, the detailed mechanism is not fully elucidated. In this study, it is shown that MSC‐derived apoptotic vesicles (apoVs) can ameliorate multiple organ dysfunction and improve survival in septic mice. Mechanistically, it is found that tail vein‐infused apoVs mainly accumulate in the bone marrow of septic mice via electrostatic charge interactions with positively charged neutrophil extracellular traps (NETs). Moreover, apoVs switch neutrophils NETosis to apoptosis via the apoV‐Fas ligand (FasL)‐activated Fas pathway. In summary, these findings uncover a previously unknown role of apoVs in sepsis treatment and an electrostatic charge‐directed target therapeutic mechanism, suggesting that cell death is associated with disease development and therapy. Abstract : Apoptotic vesicles (ApoVs) are recruited by neutrophil extracellular traps (NETs) via electrostatic charge interaction in the bone marrow. ApoVs can mediate the cell death pattern switch of neutrophils from NETosis to apoptosis via the Fas/Fas ligand pathway, then inhibit the migration of neutrophils from bone marrow to distal organs, alleviating the organ injury, and improving the survival of septic mice.